Comparison of antifungal effect of Aloevera gel and Triphala: An in vitro study - Supreet Jain; Sheetal Mujoo; Minal Daga; Salona Kalra; Ravleen Nagi; Afshan Laheji (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the present study was to determine and compare the antifungal and inhibitory activities of various concentrations of Aloevera gel and Triphala against oral Candiada albicans. Materials and Methods: The fungi (C. albicans) were isolated from 10 patients with pseudomembranous candidiasis and patients with denture stomatitis and transferred to Sabouraud's broth, which was later incubated in Sabouraud's dextrose agar (SDA). Antifungal activity of the Aloevera gel and Triphala was tested by the disc diffusion method, and minimum inhibitory concentration was determined by the broth microdilution method. Results: The mean value for zone of inhibition for Aloevera was 3.35 ± 0.59 mm and 1.06 ± 0.41mm at 100% and 50%, respectively. For Triphala, it was 4.19 ± 0.57 mm and 1.79 ± 0.43 mm at 100% and 50%, respectively (P value < 0.001). Zone of inhibition of 100% Triphala showed higher value than that of Aloevera at the same concentration (P = 0.004). Similar results were obtained at 50% concentration of Triphala and Aloevera (P = 0.004). Minimum inhibitory concentration of Aloevera gel and Triphala against C. albicans was 25% and 12.5%, respectively. Conclusion: Aloevera gel and Triphala both showed antifungal property at higher concentrations and can be used as a promising adjunct for antifungal agents.